Me Time and Foreverism: L’Hic ET Nunc of Caregiver for People with Disabilities - Coppola, Marianna (Italian Sociological Review, 2025)
The communication of a disability diagnosis does not only concern the person directly involved, but is a critical event capable of producing profound effects on the entire support network, with particular reference to the family unit. In fact, it triggers a complex and articulated process of re-elaboration and renegotiation that affects multiple dimensions of daily life and social reality. In this process, the variable of time plays a central role and takes different forms, highlighting its polysemic and symbolically dense nature. On the one hand, time manifests itself in its tangible and factual sense: the time devoted by the caregiver to caring for the person with a disability. This time, which is often pervasive, ends up taking away time from other areas of daily life, such as work, personal interests, leisure activities and maintaining social relationships. On the other hand, time appears as an immaterial and conceptual dimension, linked to planning for the future. It is a future fraught with unknowns, in which the personal perspective of the caregiver and that of the dyadic relationship with the person being cared for are intertwined. This paper aims to explore the psychological, social and symbolic-imaginary aspects related to the perception and management of care time, the ways in which carers involved in assisting people with disabilities plan for the future, and the role and function of support networks in the management and use of time.